Integrating gender into Kenya - evolving seed policies - McEwan, Margaret (International Potato Center, 2017)
Presented by Margaret McEwan (CIP), as part of the Capacity Development Workshop hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 7-8 December 2017